Unilateral Outer Bow Expanded Cervical Headgear Force System: 3D Analysis Using Finite Element Method - Allahyar Geramy; Omid Mortezai; Masomeh Esmaily; Hojat Darvishpour (Tehran University of Medical Sciences, 2015)
Objectives: Headgears are among the effective orthodontic appliances to achieve treatment goals. Unilateral molar distal movement is sometimes needed during an orthodontic treat- ment, which can be achieved by an asymmetric headgear. Different unilateral headgears have been introduced. The main goal of this study was to analyze the force system of uni- lateral expanded outer bow asymmetric headgears by the finite element method (FEM). Materials and Methods: Six 3D finite element models of a mesiodistal slice of the maxilla containing upper first molars, their periodontal ligaments (PDLs), cancellous bone, cortical bone, and a cervical headgear with expanded outer bow attached to maxillary first molars were designed in SolidWorks 2010 and meshed in ANSYS Workbench ver. 12.1. The mod- els were the same except for the degree of outer bow expansion. The outer bow ends were loaded with 2-Newton force. The distal driving force and the net moment were evaluated. Results: A decrease in the distalizing force in the normal side molar from 1.69 N to 1.37 N was shown by increasing the degree of unilateral expansion. At the same time, the force increased from 2.19 N to 2.49 N in the expanded side molar. A net moment increasing from 2.26 N.mm to 4.64 N.mm was also shown. Conclusion: Unilateral outer bow expansion can produce different distalizing forces in mo- lars, which increase by increasing the expansion.